PRAYER AS FUNDAMENTAL AND PERSONAL RELIGIOUS ACT: A Philosophical Inquiry - Kachappilly, Kurian (Journal of Dharma, 2003)
The advent of William James (1842-1910) on the American scene marked a turning point in the approach to Philosophy of Religion. His preparation of the essays, The Will To Believe (1897) and The Varieties of Religious Experience (1902), was guided by the conviction that the significance of a belief should be judged not by its “sources, but by its fruits.” The result was a massive change of emphasis from an almost exclusive involvement with dogma and the external forms of religion to a sympathetic and respectful concern for the religious experience and its most fundamental and personal act, prayer.